Original articleThe analysis of the intrasurgical view of the obstetric brachial plexus palsy - Gosk, Jerzy; Rutowski, Roman; Rabczyński, Jerzy (Folia Neuropathologica, 2005)
The surgical intervention is necessary in about 20% of all cases of the perinatal brachial plexus palsy. In this study the intrasurgical view and the applied microsurgical techniques were analysed. The clinical material consisted of 49 children with the obstetric brachial plexus palsy treated operatively, on which the following changes were found intrasurgically: compression of the brachial plexus in 21 cases and injuries with discontinuity of the elements of the brachial plexus in 28 cases. The following surgical procedures were performed: neurolysis – 31 cases, direct neurorrhaphy – 7 cases, 2 – 4 sural nerve grafting from 2 to 3 cm – 4 cases, extraanatomical extraplexual reconstruction – 6 cases, extraanatomical intraplexual reconstruction – 1 case. In all cases the intrasurgical view motivated the operative intervention. The most important problem in treatment of the obstetric brachial plexus palsy is a separate group of children who need a surgical intervention.